2020
DOI: 10.1111/ppc.12589
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the sleep quality and potential violence among patients with schizophrenia in community

Abstract: Purpose: Sleep quality in patients with schizophrenia is correlated with potential violence. However, few studies have conducted in-depth discussions on community patients with schizophrenia. The purpose of this study was to explore the influences of demographic characteristics, psychiatric symptom severity, and sleep quality in community patients with schizophrenia on the risks of potential violence and its subdimensions (ie, physical aggression, verbal aggression, anger, and hostility).Design and Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that various demographic characteristics are associated with violent behavior in schizophrenia, including: male sex ( 13 , 14 ), non-adherence to treatment ( 15 ), substance abuse ( 1 , 2 , 16 18 ), younger age ( 13 ), history of violence ( 2 , 15 , 19 ), personality disorders ( 20 ), and childhood trauma ( 21 23 ). Clinical risk factors of violent behavior in patients with schizophrenia are anxiety ( 19 ), poor sleep quality ( 24 , 25 ), hallucination and delusion ( 26 , 27 ), poor insight ( 26 , 28 ), and impulsivity ( 29 ). However, conclusions are still inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that various demographic characteristics are associated with violent behavior in schizophrenia, including: male sex ( 13 , 14 ), non-adherence to treatment ( 15 ), substance abuse ( 1 , 2 , 16 18 ), younger age ( 13 ), history of violence ( 2 , 15 , 19 ), personality disorders ( 20 ), and childhood trauma ( 21 23 ). Clinical risk factors of violent behavior in patients with schizophrenia are anxiety ( 19 ), poor sleep quality ( 24 , 25 ), hallucination and delusion ( 26 , 27 ), poor insight ( 26 , 28 ), and impulsivity ( 29 ). However, conclusions are still inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with schizophrenia are more likely to exhibit violent behavior, compared with the general population. The relationship of schizophrenia and violent behavior has been repeatedly reported (1)(2)(3). Violent behaviors committed by patients with schizophrenia, not only cause physical damage or death to people, but also increase the social burden (4).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from schizophrenia are very relevant to delusional disorders because of the considerable overlap between the two disorders. In schizophrenia, sleep quality has been correlated with the degree of paranoid ideation [ 36 ], with hostility and violence [ 37 ], with poor quality of life [ 38 , 39 ], with memory functions [ 40 ], with physical activity [ 41 ], and with dopamine signaling [ 42 ]. These correlations may well also apply to DD.…”
Section: Sleep and Psychosismentioning
confidence: 99%